An Overview of Pharmacological and Clinical Aspects of Spirulina - Ansari, Ramin; Foroughinia, Farzaneh; Dadbakhsh, Amir H.; Afsari, Forough; Zarshenas, Mohammad Mehdi (Current Drug Discovery Technologies, 2023)
Spirulina or Arthrospira, a Cyanobacterium from the class Cyanophyceae, with a wide range of properties, has been applied for over 400 years. The present study aimed to review available investigations surrounding the clinical and pharmacological properties of Spirulina that have been carried out so far. Databases including Scopus, PubMed, Google Scholar, and Web of Science were searched for relevant literature using the keywords: (Spirulina), (pharmacology), and (clinical). About 130 papers that studied the pharmacological characteristics of Spirulina in animal models, as well as clinical trials, were selected from the beginning to 29 July 2021. According to this review, antioxidative, anti-inflammatory, anti-neoplastic, hypolipidemic, antiviral, immunomodulatory, antimicrobial, anti-atherogenic, anti-diabetic, and radio-protective functions are attributed to Spirulina. Moreover, Spirulina's positive influence on several organs, including hair, skin, liver, CNS, lung, and genitourinary tract, are ascribed to different components of various species of Spirulina such as Spirulina platensis, Spirulina fusiformis, and Spirulina maxima. Although so many studies have been accomplished on every aspect of Spirulina in recent years, the lack of a comprehensive investigation surrounding this microalga encouraged us to prepare this paper. Therefore, the present study could be considered an up-to-date overview of the clinical, pharmacological, and molecular aspects of Spirulina, resulting in more occupational research on this valuable organism.
Keywords: pharmacology